The Influence of Sustainable Innovation, Digital Technology, and Promotion on Sales Performance of Sigiro Art Shop - Mario Andrias Kiton; Agusman; Brian Valentino Sigiro (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the influence of sustainable innovation, digital technology, and promotion on the sales performance of Sigiro Art Shop MSMEs. The background of this research is based on the importance of improving MSME competitiveness through product innovation, the utilization of digital technology, and effective promotional strategies in facing increasingly dynamic market competition. Sigiro Art Shop is an MSME engaged in the production and sale of traditional Karo musical instruments, particularly traditional and electric kulcapi, which have experienced fluctuating sales during the research period. This study employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to respondents who had direct relationships with Sigiro Art Shop. The data were analyzed using multiple linear regression with the assistance of SPSS software, including validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that sustainable innovation, digital technology, and promotion have a positive and significant effect on the sales performance of Sigiro Art Shop, both partially and simultaneously. These findings suggest that improving product innovation, maximizing the use of digital technology, and implementing effective promotional activities can increase sales and strengthen the competitiveness of culture-based MSMEs. Therefore, Sigiro Art Shop should continuously develop innovation, expand the utilization of digital technology, and enhance promotional effectiveness to support sustainable business growth